Perkembangan Riset Desain Sistem Informasi Menggunakan Pendekatan Terstruktur : Sistematic Literature Review - Yerik Afrianto Singgalen (Journal of Information System and Informatics, 2021)
This article aims to analyze the dynamics of information systems design using a structured model, based on the year of publication, the scope of application of information systems, and the information system platform designed (website, desktop, mobile). The method adopted is a literature study using a Systematic Literature Review (SLR) approach. The supporting instrument used in the literature study was the Nvivo 12 Plus. The articles that are evaluated are limited to journals indexed by Garuda (garuda.ristekbrin.go.id) from 2010-2021. The results of the evaluation of structured model-based information system design are classified based on three characteristics of information systems, namely: website-based information systems; desktop; and mobile. The classification based on case studies of information system design consists of five characteristics of institutions, namely government institutions; educational institutions; health institutions; profit institutions; and non-profit organizations. Tools evaluated are limited to Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). Based on the results of the literature study, it can be seen that the design of information systems based on a structured approach using Data Flow Diagrams (DFD) has increased in 2018 and 2019. Meanwhile, database system design using a structured approach-based Entity Relationship Diagram (ERD) has increased in 2019. The most studied scope of application of information systems based on the characteristics of institutions is profit institutions, educational institutions, and government agencies.